Corporate Governance - Frey, William; Cruz-Cruz, Jose a (Open textbook library., 2014)
This course takes an interdisciplinary approach to ethics in business and provides modules in Ethical Leadership, Ethical Decision-Making, Social Responsibility, and Corporate Governance. Students will actively study ethical theory by carrying out exercises to help them build theory-based tools for encountering ethical problems in business practice. They will also work with cases in business ethics designed to give them practice in developing skills of ethical leadership, ethical decision-making, and carrying out socio-technical analyses to respond to issues of social responsibility. This course will culminate in an Ethics Bowl competition in which students will practice ethics advocacy in a variety of organizational contexts in business.